Key technology and solution of intelligent resolution for the huge carrier DNS - Wei PENG; Weihua CAO; Xiaodong HE (Dianxin kexue)
The principles and advantages of intelligent DNS resolution were mainly analyzed.The carrier DNS's intelligent resolution was studied,such as the key intelligent resolution techniques of cache server,recursion server and cache view.According to the characteristics of huge telecom carrier's network,a solution of intelligent resolution,which can provide reference for the development and optimization of huge telecom carrier DNS was proposed.